The shakespeare stealer - Blackwood, Gary L. (New York : Dutton Children's Books, 1998)
A young orphan boy is ordered by his master to infiltrate Shakespeare's acting troupe in order to steal the script of "Hamlet," but he discovers instead the meaning of friendship and loyalty.
Sequel: Shakespeare's scribe.
Keywords: Shakespeare, William, -- 1564-1616 -- Fiction; Theater -- Fiction; Orphans -- Fiction; Actors and actresses -- Fiction; Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction